Digital evaluation of the leaf wall area of the grapevine (Vitis vinifera cv. Sauvignon) by using LIDAR measuring technology - Berk, Peter (Array, 2021)
A dosage rate reduction of plant protection products mixed with water, i.e. spray mixture, in a prescribed concentration in the vineyard will only be possible in the future, if the natural characteristics of vine canopy structures (leaf wall area) and canopy management are taken into account. In a practical experiment in the vineyard we evaluated the leaf wall area of the vine cv. Sauvignon on different segments on the left and right side of the vine canopy. We compared the results of manual measurements and laser measuring technology (LIDAR) with the corresponding algorithm, with which we enabled the digital reconstruction of the leaf wall area of the vine. The manual measurement of the leaf wall area was carried out using an automated image analyser. The digital system for measuring the leaf wall area on different segments consisted of a LIDAR sensor and a Differential Global Positioning System (hereinafter DGPS). To determine the exact DGPS position of the LIDAR sensor during the measurement, we set up a DGPS base station. Using the Excel software (CORREL function), we estimated the relationship between the dependent variable (digital number of points in the cloud) and an independent variable (leaf wall area, manually measured). An analysis of six randomly selected vines in the vineyard revealed the maximum value of the correlation coefficient r = 0.80 for the left side and r = 0.90 for the right side of the leaf wall area of the vine, respectively. In the near future the virtual three-dimensional space will provide more even control of spray mixture over the entire structure of the leaf wall area in the vineyard based on autonomous decision-making models.